Assessment of the gustatory function in patients with advanced oral cavity and oropharyngeal cancer - Cunha,Maria Deluana da (2020)
Abstract: Purpose: The changes in gustatory function resulting from oncological treatment occur mainly after radiotherapy. However, the head and neck tumors, because of the anatomical location of the lesion, can themselves trigger significant changes in the feeding-related functions - including taste. To assess the gustatory function in patients diagnosed with advanced oral cavity and oropharyngeal cancer. Method: This descriptive cross-sectional study comprised 31 individuals with advanced oral cavity and oropharyngeal cancer, referred for oncological treatment with radiotherapy, either alone or in combination with chemotherapy. The “taste strips” test was applied; it consists of inserting solutions with four different concentrations each for salty, sweet, and sour tastes, and three concentrations for the bitter taste, on the tongue. Results: Most of the individuals were diagnosed with oropharyngeal cancer. Approximately half of the sample already had taste-related complaints, and more than 80%, swallowing-related complaints. The overall frequency of hypogeusia was 38.7%, in which the bitter taste stood out in its isolated assessment. The association of change in gustatory function proved to be significant in patients in stage T4. Conclusion: The decrease in gustatory function in individuals with oral cavity and oropharyngeal cancer was evidenced in this study, especially when associated with tumors in stage T4. Regarding feeding, most of them reported complaints of dysphagia, suggesting the importance of the speech-language-hearing assessment and follow-up, even before the oncological treatment, to minimize the risks of dysphagia.